Keterlambatan Berbicara pada Anak Usia 4 Tahun - Wahyu Oktavia; Anisa Nurcholifah (Ma Chung Press, 2019)
This paper focuses on the language disorder in the form of speech delay, which happens to five-year-old children. This research was conducted with the aim to describe: 1) Factors that influence speech delay in children, 2) The treatment given by parents and environment in response to the problem of speech delay (speech delay) in children. Data retrieval is done by listening and recording data from a YouTube video. In data analysis techniques, researchers used qualitative methods. Technique of presentation of result of data analysis used is method of informal presentation because its data is speech. Based on the results of data analysis, it can be concluded that there are many inhibiting factors in children's speaking ability, among which are (1) hearing impediment, (2) developmental obstacles in the brain mastering oral-motor, (3) heredity problems, (4) learning problems and communication with parents, and (5) Media factors in this case television. Therefore, the role of parents, teachers, and the environment is very important in improving the ability to speak at early childhood. Then special treatment needs to be done by parents and the surrounding environment by changing the language used when talking to the child.